Mark Twain : A Life - Powers, Ron (New York Free Press, 2006)
Presents a biography of nineteenth-century American writer and humorist, Mark Twain, and chronicles his personal and professional life, including information on the landscape and events of his day, describing Twain as he lived.
Include Bibliography and Index
Keywords: Authors, American -- Humorists, American -- Twain, Mark, 1835-1910